Playing Music May Improve the Gait Pattern in Patients with Bilateral Caloric Areflexia Wearing a Cochlear Implant: Results from a Pilot Study - Hallemans, Ann; Mertens, Griet; Van de Heyning, Paul; Van Rompaey, Vincent (Frontiers in Neurology, 2017)
Hypothesis Auditory information through an active cochlear implant (CI) influences gait parameters in adults with bilateral caloric areflexia and profound sensorineural hearing loss. Background Patients with bilateral caloric areflexia suffer from imbalance, resulting in an increased risk of falling. In case of simultaneous deafness, the lack of auditory feedback results in less awareness of the auditory scene. This combination might produce significant challenges while walking and navigating. Auditory cues can be restored to some extent with a CI. Electrical stimulation through a CI can also produce a vestibulocollic reflex through current spread, which can be measured as cervical vestibular-evoked myogenic potentials. Methods Adults (seven males, one female, mean age 61 ± 14 years), wearing a CI to treat profound sensorineural hearing loss and presenting with bilateral caloric areflexia walked barefoot, over ground, at self-selected speed in three different conditions: with CI turned on, while listening to music and with CI turned off. Spatiotemporal and kinematic parameters of gait were calculated using the conventional gait model. Results Removing auditory feedback by turning off the CI decreased stride time (mean difference 0.03 ± 0.15 s) and slightly increased stride length (mean difference 0.5 ± 1.2 cm) compared to the control condition with the CI on. Walking while playing music positively affected gait compared to walking with the CI on but without auditory feedback. By increasing the motion of the pelvis (mean difference 1.3° ± 0.4°), the knee (mean difference 3.9° ± 0.8°) and the ankle (mean difference 2.2° ± 0.2°), stride length increased (7.8 ± 1.2 cm), while stride time decreased (0.059 ± 0.016 s). Conclusion Although a practice effect cannot be completely ruled out, this pilot study suggests that playing music while wearing an active CI may improve gait in patients with bilateral otovestibular loss. It remains unclear if the musical cues boost balance control or the CI might produce current spread and electrical stimulation to the vestibular afferents, thereby boosting its detection threshold, through stochastic resonance, and improving gait.